The Transvaluation of “Soul” and “Spirit”: Platonism and Paulism in H.P. Blavatsky’s Isis Unveiled - Plaisance, Christopher A (Pomegranate, 2014)
This paper in the doxographic history of Western esotericism examines H.P. Blavatsky's use of the terms “soul” and “spirit” in Isis Unveiled. “Soul” and “spirit” have been given great importance both in early Greek thought and throughout the subsequent history of Western philosophy, religion, and science, and uses of these terms are generally bound up with the attributions of one Greek school or another. As Isis Unveiled specifically frames itself as a “Hermetic” work, it would be reasonable to assume that Blavatsky’s early use of “soul,” “spirit,” and their cognates in other languages would comport to the usage of the Alexandrian Hermetists—who phrased the relationship between the two in terms of spirit being distinct from and inferior to soul, with spirit acting as an intermediary substance which bridges the gap in the emanative descent from the soul to body. However, Blavatsky’s use both of the English and Greek terms (as well as their Latin equivalents) curiously follow an inversion of this usage. As such, the principal purpose of this study is to examine her understanding of these terms, and of the sources to which she appeals in an attempt to uncover how and why this transvaluation occurred. This is accomplished by first examine Blavatsky’s usage, and then those of the historical precedents, charting the semantic shift from antiquity to that of Isis Unveiled.